Xp21 contiguous gene deletion syndrome presenting as congenital adrenal hypoplasia: molecular diagnosis and clinical re-evaluation of a pedigree - Donghua Zhang; Wenchun Li; Mei Li; Yinghong Lu; Sisi Ning; Xiafei Liang; Yuling Xie; Yunrong Qin (Frontiers in Endocrinology, 2026)
Objective To investigate the molecular etiology in a male child clinically suspected of congenital adrenal hyperplasia (CAH) with negative conventional genetic testing, and to elucidate the genetic characteristics of his pedigree. Methods Clinical data from the proband and his family members were collected. Molecular diagnostics proceeded sequentially: initial targeted CAH testing ( CYP21A2 and POR sequencing/MLPA, plus targeted NR0B1 CNV analysis) was followed by whole-exome sequencing coupled with genome-wide CNV analysis. Results The proband presented with neonatal cyanosis and hyperpigmentation. Laboratory tests showed markedly elevated ACTH (354.68 pmol/L) and low aldosterone (57.24 pg/mL). Molecular genetic testing identified a hemizygous deletion of approximately 4.44 Mb at Xp21.3-p21.1 (chrX:g.27080000_31520000), encompassing the NR0B1 , GK , IL1RAPL1 , and DMD genes. CNV-seq confirmed that the mother carried a heterozygous deletion of 4.38 Mb in the same region, while the father and four maternal aunts showed normal genotypes. Conclusion This study ultimately diagnosed the proband with Xp21 contiguous gene deletion syndrome. The adrenal insufficiency resulted from X-linked congenital adrenal hypoplasia (AHC) due to NR0B1 haploinsufficiency, rather than CAH. These findings highlight the considerable clinical overlap between AHC and CAH, indicating that CNV analysis of the Xp21 region should be included in the diagnostic workup for male infants with suspected CAH but negative routine genetic testing. This provides a basis for the precise diagnosis and genetic counseling of such patients.